The Cultural Dependence of Vocational Training. - Beck, N; Kabst, Rüdiger; Walgenbach, P (Journal of International Business Studies (JIBS).)

Elektronische Wahlen: Verifizierung vs. Zertifizierung - Volkamer, Melanie; Schryen, Guido; Langer, Lucie; Schmidt, Axel; Buchmann, Johannes (Workshop Elektronische Wahlen, elektronische Teilhabe, Societyware, 39th GI-Jahrestagung)
Der Beitrag diskutiert die kontroversen Ansätze ? Verifizierung versus Evaluation/Zertifizierung ? zur Sicherung elektronischer Wahlen mit Wahlgeräten. Dabei spielt das Urteils des Bundesverfassungsgerichts [BVG099] eine zentrale Rolle. Hierin wird entschieden, dass die Zertifizierung des Wahlgerätes nicht ausreicht und es werden Verifizierungsfunktionen gefordert, die den Wählern die Möglichkeit geben sich von der Integrität des Wahlergebnisses zu überzeugen. Der Beitrag zeigt auf, dass auch mit der Implementierung entsprechender Verifizierungsfunktionen nicht auf Zertifizierung verzichtet werden kann, da an ein Wahlgerät auch andere Anforderungen wie etwa hinsichtlich des Wahlgeheimnisses gestellt werden. Es wird außerdem die Frage diskutiert, warum der Zertifizierung hinsichtlich dieser zusätzlichen Anforderungen vertraut werden kann, während dies nicht der Fall bei der Integritätsanforderung ist.

Security in Large-Scale Internet Elections: A Retrospective Analysis of Elections in Estonia, The Netherlands, and Switzerland - Schryen, Guido; Rich, Eliot (IEEE Transactions on Information Forensics & Security)
Remote voting through the Internet provides convenience and access to the electorate. At the same time, the security concerns facing any distributed application are magnified when the task is so crucial to democratic society. In addition, some of the electoral process loses transparency when it is encapsulated in information technology. In this paper, we examine the public record of three recent elections that used Internet voting. Our specific goal is to identify any potential flaws that security experts would recognize, but may have not been identified in the rush to implement technology. To do this, we present a multiple exploratory case study, looking at elections conducted between 2006 and 2007 in Estonia, Netherlands, and Switzerland. These elections were selected as particularly interesting and accessible, and each presents its own technical and security challenges. The electoral environment, technical design and process for each election are described, including reconstruction of details which are implied but not specified within the source material. We found that all three elections warrant significant concern about voter security, verifiability, and transparency. Usability, our fourth area of focus, seems to have been well-addressed in these elections. While our analysis is based on public documents and previously published reports, and therefore lacking access to any confidential materials held by electoral officials, this comparative analysis provides interesting insight and consistent questions across all these cases. Effective review of Internet voting requires an aggressive stance towards identifying potential security and operational flaws, and we encourage the use of third party reviews with critical technology skills during design, programming, and voting to reduce the changes of failure or fraud that would undermine public confidence.
Keywords: e-voting; Internet voting; Internet election; security; verifiability; RIES; Estonia; Neuchâtel

Open Source vs. Closed Source Software: Towards Measuring Security - Schryen, Guido; Kadura, Rouven (24th Annual ACM Symposium on Applied Computing)
The increasing availability and deployment of open source software in personal and commercial environments makes open source software highly appealing for hackers, and others who are interested in exploiting software vulnerabilities. This deployment has resulted in a debate ?full of religion? on the security of open source software compared to that of closed source software. However, beyond such arguments, only little quantitative analysis on this research issue has taken place. We discuss the state-of-the-art of the security debate and identify shortcomings. Based on these, we propose new metrics, which allows to answer the question to what extent the review process of open source and closed source development has helped to fix vulnerabilities. We illustrate the application of some of these metrics in a case study on OpenOffice (open source software) vs. Microsoft Office (closed source software).
Keywords: Open source software; Closed source software; Security; Metrics

A comprehensive and comparative analysis of the patching behavior of open source and closed source software vendors - Schryen, Guido (5th International Conference on IT Security Incident Management & IT Forensics)
While many theoretical arguments against or in favor of open source and closed source software development have been presented, the empirical basis for the assessment of arguments is still weak. Addressing this research gap, this paper presents a comprehensive empirical investigation of the patching behavior of software vendors/communities of widely deployed open source and closed source software packages, including operating systems, database systems, web browsers, email clients, and office systems. As the value of any empirical study relies on the quality of data available, this paper also discusses in detail data issues, explains to what extent the empirical analysis can be based on vulnerability data contained in the NIST National Vulnerability Database, and shows how data on vulnerability patches was collected by the author to support this study. The results of the analysis suggest that it is not the particular software development style that determines patching behavior, but rather the policy of the particular software vendor.

Security of open source and closed source software: An empirical comparison of published vulnerabilities - Schryen, Guido (15th Americas Conference on Information Systems)
Reviewing literature on open source and closed source security reveals that the discussion is often determined by biased attitudes toward one of these development styles. The discussion specifically lacks appropriate metrics, methodology and hard data. This paper contributes to solving this problem by analyzing and comparing published vulnerabilities of eight open source software and nine closed source software packages, all of which are widely deployed. Thereby, it provides an extensive empirical analysis of vulnerabilities in terms of mean time between vulnerability disclosures, the development of disclosure over time, and the severity of vulnerabilities, and allows for validating models provided in the literature. The investigation reveals that (a) the mean time between vulnerability disclosures was lower for open source software in half of the cases, while the other cases show no differences, (b) in contrast to literature assumption, 14 out of 17 software packages showed a significant linear or piecewise linear correlation between time and the number of published vulnerabilities, and (c) regarding the severity of vulnerabilities, no significant differences were found between open source and closed source.
Keywords: Vulnerabilities; security; open source software; closed source software; empirical comparison

Individuelle Förderung - Einblicke in Strukturen und erste empirische Ergebnisse des Modellprojekts InLab - Beutner, Marc; Frehe, Petra; Kremer, H.-Hugo; Zoyke, A. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Berufsbildung im Justizvollzug - Das Projekt TANDEM - Beutner, Marc; Gebbe, M.; Kremer, H.-Hugo (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Individuelle Förderung von Kompetenzen - Curriculare und didaktisch-methodische Optionen - Kremer, H.-Hugo; Zoyke, Andrea (Erziehungswissenschaft und Beruf)

Bewältigung beruflicher Übergänge im Lebensverlauf - Kremer, H.-Hugo (Bildungsperspektiven in alternden Gesellschaften)

Performative Lebensbewältigung in alternden Gesellschaften: Projektbeschreibung und Einführung in den Tagungsband - Dehmel, A.; Kremer, H.-Hugo; Schaper, N.; Sloane, Peter F. E. (Bildungsperspektiven in alternden Gesellschaften)

Implementation von E-Learning an Berufskollegs - eine Studie zu Stand und Entwicklungsperspektiven in Ostwestfalen-Lippe - Kremer, H.-Hugo; Zoyke, A. (Wirtschaft und Erziehung)

Comparing Architectural Styles for Service-Oriented Architectures – a REST vs. SOAP Case Study - Becker, Jörg; Matzner, Martin; Müller, Oliver (Information Systems Development)

Documentation of flexible business processes-A healthcare case study - Becker, Jörg; Bergener, Katrin; Müller, Oliver; Müller-Wienbergen, Felix (Americas Conference on Information Systems)

A design research study on enhancing creativity-The case of developing product-service bundles - Müller-Wienbergen, Felix; Seidel, Stefan; Müller, Oliver; Knackstedt, Ralf; Becker, Joerg (European Conference on Information Systems)

Cross-Border Group-Taxation and Loss-Offset in the EU - An Analysis for CCCTB (Common Consolidated Corporate Tax Base) and ETAS (European Tax Allocation System) - Dahle, Claudia; Bäumer, Michaela

Der Einfluss der Abgeltungssteuer auf die Vorteilhaftigkeit von Anlagen in Genussscheine und Aktien - Halberstadt, Alexander; Sureth-Sloane, Caren; Voß, Armin (Die Wirtschaftsprüfung)

Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren

Umsatzsteuerausfall und Umsatzsteuerbetrug - Eine steuerökonomische Analyse der Umsatzsteuerdeklaration - Nordhoff, Daniel

Strukturprobleme angehen - Nordhoff, Daniel; Popp, Matthias (Niedersächsische Wirtschaft)

Verschärfung der Verlustabzugsbeschränkung durch § 8c KStG und deren Einfluss auf den Erwerb von Anteilen an Kapitalgesellschaften - Sureth-Sloane, Caren; Vollert, Pia

Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren (Festzeitschrift für Franz W. Wagner: Accounting, Taxation, and Corporate Governance)

Social Search: Exploring and Searching Social Architectures in Digital Networks - Trier, Matthias; Bobrik, Annette (IEEE Internet Computing)

Enabling social media content quality assurance using social network analysis - Sanmateu, Maria-Amparo; Trier, Matthias; Lienicke, Andreas; Rederer, Andreas (9th International Conference On Innovative Internet Community Systems I2CS 2010)

Content-based Community Detection in Social Corpora - Bobrik, Annette; Trier, Matthias (Proceedings Wirtschaftsinformatik)

Odp2cp – ein rapid E-Learning Ansatz zur einfachen Produktion Scorm-konformer Lerninhalte - Trier, Matthias; Herzog, Michael; Möller, Daniel (Proceedings Wirtschaftsinformatik)

Studentische Modulevaluation - Methoden, Ergebnisse und Schlussfolgerungen aus statistischer Sicht - Lück, Sonja

Spieltheoretische Anmerkungen zur Förderung universitärer Spitzenforschung im Rahmen der Exzellenzinitiative - Kraft, Manfred; Brunn, Hans-Georg; Lück, Sonja (Bildungsökonomie in der Wissensgesellschaft)

China's provincial disparities and the determinants of provincial inequality - Gries, Thomas; Redlin, Margarete (Journal of Chinese Economic and Business Studies)

Consolidation in banking and financial stability in Europe: Empirical evidence - Uhde, André; Heimeshoff, Ulrich (Journal of Banking & Finance)
Using aggregate balance sheet data from banks across the EU-25 over the period from 1997 to 2005 we provide empirical evidence that national banking market concentration has a negative impact on European banks’ financial soundness as measured by the Z-score technique while controlling for macroeconomic, bank-specific, regulatory, and institutional factors. Furthermore, our analysis reveals that Eastern European banking markets exhibiting a lower level of competitive pressure, fewer diversification opportunities and a higher fraction of government-owned banks are more prone to financial fragility whereas capital regulations have supported financial stability across the entire European Union.
Keywords: Market structure; Financial stability; Banking regulation

Bilanzpolitisches Potential im Rahmen der Goodwillbilanzierung - Transaktionsgestaltung beim Unternehmenserwerb - Ebert, Michael; Simons, Dirk (KoR : Zeitschrift für internationale und kapitalmarktorientierte Rechnungslegung)

International corporate reporting: A comparative approach, by Clare Roberts, Pauline Weetman and Paul Gordon (fourth edition) - Kosi, Urska (The International Journal of Accounting)

Versinkt die Kapitalmarkttheorie in logischen Widersprüchen, oder: Ist arqus e.V. aus dem Schneider? - Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf J.; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Niemann, Rainer; Schanz, Deborah; Sureth-Sloane, Caren; Treisch, Corinna (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung)

Der Einfluss von Internationalisierung, Vermögens- und Kapitalstruktur auf die Konzernsteuerquote im Branchenvergleich - eine empirische Analyse - Sureth-Sloane, Caren; Halberstadt, Alexander; Bischoff, Dennis (Steuer und Wirtschaft)

Income Tax Analysis: A Comparison of Microsimulation versus Group Simulation - Müller, Heiko; Sureth-Sloane, Caren (International Journal of Microsimulation)

Unintended effects of referral reward programs: Exploring the impact of rewards on opportunistic behavior - Garnefeld, I.; Münkhoff, Eva; Hogreve, J.; Eggert, A. (38th EMAC Annual Conference, Nantes)

Referral reward programs: New customer acquisition by opportunism? - Garnefeld, I.; Münkhoff, Eva; Hogreve, J.; Eggert, A. (15th AMS World Marketing Congress, Oslo)

Integrierte Investitionsplanung in Supply Chains - Heitmann, Ingmar

Stable governments and the semistrict core - Dimitrov, Dinko; Haake, Claus-Jochen (Games and Economic Behavior)

The Shapley value of phylogenetic trees - Haake, Claus-Jochen; Kashiwada, Akemi; Su, Francis Edward (Journal of Mathematical Biology)

Two support results for the Kalai–Smorodinsky solution in small object division markets - Haake, Claus-Jochen (Mathematical Social Sciences)

On Maskin monotonicity of solution based social choice rules - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)

Comments on: Transversality of the Shapley value - Haake, Claus-Jochen (TOP)

Entscheidungsorientierte Planung unscharfer Erfolge von KMU in Supply Chains - Betz, Stefan (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

Analyse des Bullwhip-Effekts in einer Supply Chain von KMU - Betz, Stefan (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand

Reference Models and Modeling Languages for Product-Service Systems --- Status-Quo and Perspectives for Further Research - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Proceedings of the 41th Hawai'i International Conference on System Sciences)

Modeling, Customer-Specific Configuration and Calculation of Value Bundles - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Americas Conference on Information Systems)

Konfigurative Prozessmodellierung der hybriden Leistungserstellung in Unternehmensnetzwerken des Maschinen- und Anlagenbaus - Beverungen, Daniel; Kaiser, Uwe; Knackstedt, Ralf; Krings, Robin; Stein, Armin (Proceedings of the Multikonferenz Wirtschaftsinformatik (MKWI 2008))

Improving the Quality of Article Master Data --- Specification of an Integrated Master Data Platform for Promotions in Retail - Winkelmann, Axel; Beverungen, Daniel; Janiesch, Christian; Becker, Jörg (Proceedings of the 16th European Conference on Information Systems)